Economic Growth In India – Travel Tourism & Hospitality: Exploring the Impact of Travel Tourism on Economic Growth in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Travel Tourism is concernedwith pleasure ,  holidays, travel andgoing or somewhere. Tourism involves the movements of people to and  their stay at various destinations. Thisinvolves a journey and services like transport, accommodation, catering andviewing etc. The activity or practice of touring ,the business of industry ofproviding information, accommodations, transportation and other services totourist and the promotion of tourist travel , especially for commercialpurposes.